2008
DOI: 10.5194/aab-51-216-2008
|View full text |Cite
|
Sign up to set email alerts
|

Yield and composition of milk from Polish Holstein-Friesian and Jersey cows in particular months of the first lactations as dependent on milk protein polymorphism (short communication)

Abstract: Abstract. The experiment was performed on 121 primiparous Polish Holstein-Friesian (PHF) cows and 36 primiparous Jersey (JER) cows. The highest decrease in casein yield was noted in JER cows at 7.36 % on day 90 of lactation, 15.95 % on day 150, 26.78 % on day 210, 37.01 % on day 270 and 39.67 % on day 330. In PHF cows this decrease was substantially lower, at 4.98 %, 7.65 %, 8.72 %, 10.50 % and 16.19 % respectively. The casein content of milk from primiparous PHF cows ranged from 2.38 % (LGB – day 60) to 3.09 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This was confirmed by Silvestre et al (2009), who applied Wood's model (Wood, 1976) instead of Wilmink's. At the same time, Miciński et al (2008) found a decrease in total CN and whey protein yields from the first to the last stage of lactation in a Jersey population, whereas the patterns for the Holstein-Friesians were more similar to a zenith curve.…”
Section: Pattern Of Milk Proteins Throughout Lactationmentioning
confidence: 77%
“…This was confirmed by Silvestre et al (2009), who applied Wood's model (Wood, 1976) instead of Wilmink's. At the same time, Miciński et al (2008) found a decrease in total CN and whey protein yields from the first to the last stage of lactation in a Jersey population, whereas the patterns for the Holstein-Friesians were more similar to a zenith curve.…”
Section: Pattern Of Milk Proteins Throughout Lactationmentioning
confidence: 77%
“…Research on milk protein genes conducted in recent years (Czerwińska-Piotrowska, Kamieniecki, 2004;Czerwińska-Piątkowska et al, 2004;Feleńczak et al, 2000;Juszczak et al, 2001;Miciński et al, 2008;Pytlewski et al, 2004;Tsiaras et al, 2005;Ziemiński et al, 2005;Litwińczuk et al, 2006) yielded ambiguous results, which were mainly affected by the living conditions and nutrition of animals, as well as used statistical models.…”
Section: Introductionmentioning
confidence: 99%